IMPACT Projections of Aggregate Food Production With and Without Climate Change: Extended Country-Level Results for 2022 GFPR Table 1A - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
Policy makers, analysts, and civil society face increasing challenges to reducing hunger and sustainably improving food security. Modeling alternative future scenarios and assessing their outcomes can help inform policy choices. The International Food Policy Research Institute’s IMPACT model is an integrated system of linked economic, climate, water, and crop models that allows for the exploration of such scenarios. The IMPACT model was used to evaluate impacts of climate change on aggregate food production, food consumption (kcal per person per day), net trade of major food commodity groups, and the population at risk of hunger. At IMPACT’s core is a partial equilibrium, multimarket economic model that simulates national and international agricultural markets. Links to climate, water, and crop models support the integrated study of changing environmental, biophysical, and socioeconomic trends, allowing for in-depth analysis of a variety of critical issues of interest to policymakers at national, regional, and global levels. IMPACT benefits from close interactions with scientists across CGIAR and other leading global economic modeling efforts around the world through the Agricultural Model Intercomparison and Improvement Project (AgMIP). This dataset summarizes results from the latest IMPACT projections to 2030 and 2050, for a scenario that includes the impacts of climate change and a “baseline” scenario that assumes no climate change (for comparison). These results update previous projections by showing aggregations to six regions: Central and West Asia and North Africa; Eastern and Southern Africa; Latin America and the Caribbean; South Asia; Southeast Asia; West and Central Africa; and the rest of the world.